2010
DOI: 10.1590/s1806-83242010000200014
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries in the primary dentition of a Colombian population according to the ICDAS criteria

Abstract: This paper describes the results of a cross-sectional study conducted with a randomized sample of 447 low-income children between 2.5 and 4 years of age selected from the files of a health institution in Medellin, Colombia. The patients were examined in 2007 using the modified criteria of the International Caries Detection and Assessment System (ICDAS); the first caries code was not used. Clinical examination was carried out by three examiners previously trained in the ICDAS. The inter-examiner agreement was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 11 publications
1
46
1
8
Order By: Relevance
“…18 Similar results were obtained by Cadavid et al based on the examination of 447 children (mean age of 2.8 ±0.48 years). 19 According to Al-Malik et al, 26% of children had tooth decay restricted to the posterior teeth, 6% in the anterior teeth only, and 39% in both groups. 17 In the study of Chinese children aged 3-5, it was found that dental caries are more common in mandibular molars than in maxillary molars and in anterior maxillary teeth (23%) than anterior mandibular teeth (2% only).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…18 Similar results were obtained by Cadavid et al based on the examination of 447 children (mean age of 2.8 ±0.48 years). 19 According to Al-Malik et al, 26% of children had tooth decay restricted to the posterior teeth, 6% in the anterior teeth only, and 39% in both groups. 17 In the study of Chinese children aged 3-5, it was found that dental caries are more common in mandibular molars than in maxillary molars and in anterior maxillary teeth (23%) than anterior mandibular teeth (2% only).…”
Section: Discussionmentioning
confidence: 98%
“…23 It should be emphasized that in agreement with our results, studies conducted by other authors confirm a higher incidence of caries in the upper anterior teeth than the lower teeth. 16,18,19,21,24 It is believed that the incidence of caries in the upper arch is associated with lower flow and protection of saliva of the maxillary teeth. 16 The present study found that the predominant proportion of dmft values was caused by untreated carious lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Bivariate Poisson regression analysis with robust variance was used to determine the significance of associations between the independent variables and parental guilt (p < 0.05). The multivariate model followed a hierarchical approach from distal to proximal determinants on three levels: [1] socio-demographic data; [2] health perceptions; and [3] oral health problems (Figure  1) [30]. On each level, the backward stepwise method was used for the selection of variables having with a p-value < 0.20 in the bivariate analysis as well as variables considered epidemiological determinants.…”
Section: Methodsmentioning
confidence: 99%
“…Despite advances in the prevention and treatment of oral health problems, high prevalence rates of dental caries [1, 2] and traumatic dental injury (TDI) [3, 4] continue to be found among preschool children. These conditions can have a negative impact on the oral health-related quality of life (OHRQoL) of the family [57], since parents feel responsible for their child’s oral health [8].…”
Section: Introductionmentioning
confidence: 99%
“…En Colombia se han reportado cifras variables, llegando a afectar más de tres cuartas partes de los niños y niñas evaluados en algunos de estos estudios [4][5][6][7], con diferentes niveles de severidad. Este problema de salud bucal es motivo de preocupación, por cuanto se tiene evidencia de que compromete el bienestar, la calidad de vida y el adecuado crecimiento y desarrollo de niños y niñas [8][9][10][11][12][13].…”
Section: Introductionunclassified